Local factors determining the response to antiangiogenic therapy with first-line drugs in macular neovascularization - V.G. Likhvantseva; S.G. Kapkova; E.B. Tretyak; S.I. Rychkova; A.S. Gevorkyan; T.E. Borisenko (РМЖ "Клиническая офтальмология")
V.G. Likhvantseva1,2, S.G. Kapkova1,2, E.B. Tretyak1, S.I. Rychkova1,3, A.S. Gevorkyan2, T.E. Borisenko4 1A.I. Burnazyan Federal Medical Biophysical Center of the Federal Medical Biological   Agency of Russia, Moscow, Russian Federation 2Academy of Postgraduate Education of the Federal Scientific and Clinical Center of the   Federal Medical Biological Agency of Russian Federation, Moscow, Russian Federation 3Institute for Information Transmission Problems of the RAS (Kharkevich Institute), Moscow,   Russian Federation 4M.M. Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation Background: the prevalence of macular neovascularization (MNV) is on the rise. However, fundamental data on systemic and local factors determining response to the treatment of MNV have not yet been studied. Aim: to analyze baseline intraocular pressure (IOP) and mean ocular perfusion pressure (mOPP) in patients with MNV in association with the response to antiangiogenic therapy. Patients and Methods: this retrospective cohort study included 84 patients (29 men, 55 women; 92 eyes) with newly diagnosed MNV and signs of disease activity. The age of the patients ranged fr om 52 to 97 years (mean age 73.4±8.5 years). In 18 (19.5%) patients, MNV was bilateral. IOP and mOPP were measured in all patients with MNV who received fixed-interval intravitreal injections of aflibercept. Treatment results were evaluated clinically and morphometrically by optical coherence tomography. Patients were allocated into five subgroups based on treatment response. A correlation analysis was performed between IOP and mOPP, on the one hand, and treatment outcomes, on the other hand. Results: improvement of MNV activity markers in the setting of treatment manifested as reduction in area and height of subretinal fluid (k=0.9432, p<0.01, and k=0.58959, p<0.001), reduction in height and area of retinal pigment epithelium (RPE) detachment (k=0.82808, p<0.05; k=0.50221, p<0.05) and reduction in sub-RPE fluid (k=0.84515, p<0.05) were strongly directly correlated with baseline IOP. The correlation between IOP and central retinal thickness was negative (k=-0.27266, p<0.05). The biomarker associated with the ideal response was IOP levels of 12.6 mmHg, the balance point, wh ere the sensitivity and specificity of poor response approximately coincided. At this IOP, the sensitivity of poor response was 0.603 and the specificity was 0.737. The IOP was found to be below 12.6 mm Hg in 40% of non-responders and 74% of responders. The 95% confidence interval limits did not overlap, thereby illustrating the reliability of the results (p=0.00784, p<0.01). The range of recommended IOP level for a good treatment response was determined as 11–21 mm Hg. Conclusions: the identification of modifiable risk factors is of paramount importance in the field of practical ophthalmology, as it increases the likelihood of a favorable outcome. Further studies are necessary to investigate the potential for modifying IOP through IOP-lowering therapy prior to intravitreal injection. Keywords: macular neovascularization, antiangiogenic therapy, risk factor, intraocular pressure, mean ocular perfusion pressure. For citation: Likhvantseva V.G., Kapkova S.G., Tretyak E.B., Rychkova S.I., Gevorkyan A.S., Borisenko T.E. Local factors determining the response to antiangiogenic therapy with first-line drugs in macular neovascularization. Russian Journal of Clinical Ophthalmology. 2024;24(2):69–77 (in Russ.). DOI: 10.32364/2311-7729-2024-24-2-5.